Continuum limit of the integrable sl(2/1) 3-(3)over-bar superspin chain - Essler, F; Frahm, H; Saleur, H (2005)
By a combination of analytical and numerical techniques, we analyze the continuum limit of the integrable 3 ⊗ 3̄ ⊗ 3 ⊗ 3̄...sl(2/1) superspin chain. We discover profoundly new features, including a continuous spectrum of conformal weights, whose numerical evidence is infinite degeneracies of the scaled gaps in the thermodynamic limit. This indicates that the corresponding conformal field theory has a non compact target space (even though our lattice model involves only finite-dimensional representations). We argue that our results are compatible with this theory being the level k = 1, "SU(2/1) WZW model" (whose precise definition requires some care). In doing so, we establish several new results for this model. With regard to potential applications to the spin quantum Hall effect, we conclude that the continuum limit of the 3 ⊗ 3̄ ⊗ 3 ⊗ 3̄... sl(2/1) integrable superspin chain is not the same as (and is in fact very different from) the continuum limit of the corresponding chain with two-superspin interactions only, which is known to be a model for the spin quantum Hall effect. The study of possible RG flows between the two theories is left for further study. © 2005 Elsevier B.V. All rights reserved.